TEST FOR SUBSTANTIVE APPRAISAL OF CONCENTRATIONS IN EU LAW – SIGNIFICANT IMPEDIMENT TO EFFECTIVE COMPETITION TEST - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Substantive rewiev of concentrations is a complex task because it determines which concentrations will be allowed and which will be prohibited. Control of concentrations is conducted ex ante and it is, therefore, of crucial importance for the examination criteria to be suited to accurately predict potential effects of concentrations to the competition on the relevant market. In EU competiton law concentrations are, generally, permissible and the large majority of them are cleared in initial Phase I investigation. The concentration will be prohibited only if it can be declared as incompatible with internal market i.e. if it would significantly impede effective competition, in the common market or in a substantial part of it, in particular as a result of the creation or strengthening of a dominant position. In Regulation 139/04 a new test for substantial appraisal of mergers was introduced – a test of significant impediment to effective competition (SIEC test). In this paper author examines development of control of concentrations in the European Union, reasons for introduction of the SIEC test and the most important features of the test.